Use of biologics and small molecule drugs for the management of moderate to severe ulcerative colitis: IG-IBD clinical guidelines based on the GRADE methodology. Issue 4 (April 2022) - Macaluso, Fabio Salvatore; Orlando, Ambrogio; Papi, Claudio; Festa, Stefano; Pugliese, Daniela; Bonovas, Stefanos; Pansieri, Claudia; Piovani, Daniele; Fiorino, Gionata; Fantini, Massimo Claudio; Caprioli, Flavio; Daperno, Marco; et al.
Abstract: The management of moderate to severe ulcerative colitis has undergone significant changes over the past 15 years due to the regulatory approval of several new drugs. In particular, following the approval of the first biological, i.e. infliximab, a number of further biological drugs, such as adalimumab, golimumab, vedolizumab and ustekinumab, and small molecules, such as tofacitinib, have been approved, thus enriching the therapeutic armamentarium for ulcerative colitis. Choice of therapy must take into consideration not only the need to induce and maintain disease remission according to the patient's profile, but also age, co-morbidities, and prior treatments. To guide these decisions, the Italian Group for the Study of Inflammatory Bowel Disease has developed clinical guidelines that supersede its earlier document from 2011. These new guidelines were developed following the GRADE methodology for rating the quality of the evidence and for determining the strength of the recommendations. This article presents the methodology and results, in the form of 20 statements with commentary on the use of the five biologics and tofacitinib for managing the intestinal manifestations of active ulcerative colitis and for maintaining remission. A separate technical review reports the analyses of the evidence upon which the present recommendations are based.